Transformation of the family under rising land pressure: A theoretical essay - Catherine Guirkinger; Jean-Philippe Platteau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
If we understand well the individualization of land tenure rules under conditions of growing land scarcity and increased market integration, much less is known about the mode of evolution of the farm-cum-family units possessing the land. Inspired by first-hand evidence from West Africa, this paper argues that these units undergo the same process of individualization governed by the same forces as property rights in land. It provides a simple theoretical account of the coexistence of different forms of family when farms are heterogenous in land endowments and technology is stagnant. The paper also offers analytical insights into the sequence following which such forms succeed each other.
Keywords: D13; O12; O13; Q15; 330; patriarchal family; land division; Africa